(untitled) (Research, Society and Development, 2025)
The objective of this study was to describe the profile of Escherichia coli infections in hospitalized patients in Brazil from 2019 to 2025, highlighting their epidemiological characteristics, resistance mechanisms, and control strategies in healthcare services. Methodology: This is an integrative review based on Evidence-Based Practice (EBP), conducted in the SciELO, PubMed, and Web of Science databases, using inclusion criteria defined between January 2019 and August 2025. Results: Ten cross-sectional studies were selected, grouped into four thematic categories: resistance profile, treatment, clinical evolution, and characteristics of the affected population. The results revealed a predominance of extended-spectrum β-lactamase (ESBL)-producing strains, a high rate of multidrug resistance, and a higher incidence in vulnerable groups, such as neonates, the elderly, immunosuppressed individuals, and cancer patients. Conclusion: It is concluded that controlling E. coli infections in the hospital setting depends on continuous epidemiological surveillance, the adoption of preventive protocols, and the rational use of antimicrobials, guided by microbiological tests. These findings reinforce the need for institutional and national policies aimed at reducing bacterial resistance and ensuring patient safety.